2020
DOI: 10.1007/s12028-020-01056-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Serial CT Imaging-Derived Features Improve Prediction of Malignant Cerebral Edema after Ischemic Stroke

Abstract: Introduction: Malignant cerebral edema develops in a small subset of patients with hemispheric strokes, precipitating deterioration and death if decompressive hemicraniectomy (DHC) is not performed in a timely manner. Predicting which stroke patients will develop malignant edema is imprecise based on clinical data alone. Head computed tomography (CT) imaging is often performed at baseline and 24-h. We determined the incremental value of incorporating imaging-derived features from serial CTs to enhance predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…That is, greater intracranial reserve may certainly reflect cerebral atrophy and biologic aging, serving as a marker of impaired resiliency with respect to eventual functional recovery after large-vessel stroke [1]. In parallel but conversely, lower intracranial reserve was a clear marker of higher risk for malignant cerebral edema in our and two other recent studies [2][3][4]. We would argue that one concern, however valid, does not negate the other.…”
supporting
confidence: 46%
“…That is, greater intracranial reserve may certainly reflect cerebral atrophy and biologic aging, serving as a marker of impaired resiliency with respect to eventual functional recovery after large-vessel stroke [1]. In parallel but conversely, lower intracranial reserve was a clear marker of higher risk for malignant cerebral edema in our and two other recent studies [2][3][4]. We would argue that one concern, however valid, does not negate the other.…”
supporting
confidence: 46%
“…It can therefore be insensitive to malignant edema when measured too early, despite significant early swelling (as assessed by other volumetric or densitometric biomarkers) and patients still being at risk for subsequent deterioration. Although relatively rare, we found that 3 of 20 patients who developed malignant edema resulting in death or requiring decompressive surgery in one cohort had no measurable midline shift at 24 h but had significant edema measurable by volumetric CSF tools [19].…”
mentioning
confidence: 82%
“…The SNIPR user interface provides tools to monitor pipeline progress and review pipeline output, enabling an interactive workflow to check output quality, tune parameters, and relaunch pipeline steps. The pipeline is being used in the large SNIPR patient cohorts to study how dynamic change in brain volumetric values can predict trajectory of edema ( Mohammadian Foroushan et al, 2020b ).…”
Section: Methodsmentioning
confidence: 99%